PedBotHome: A Video Game–Based Robotic Ankle Device Created for Home Exercise in Children With Neurological Impairments. Issue 2 (23rd April 2022) - Coley, Catherine; Kovelman, Staci; Belschner, Justine; Cleary, Kevin; Schladen, Manon; Evans, Sarah Helen; Salvador, Tyler; Monfaredi, Reza; Fooladi Talari, Hadi; Slagle, Jacob; Rana, Md Sohel
Abstract : Purpose: This pilot study assesses the feasibility of using PedBotHome to promote adherence to a home exercise program, the ability of the device to withstand frequent use, and changes in participant ankle mobility. PedBotHome is a robotic ankle device with integrated video game software designed to improve ankle mobility in children with cerebral palsy. Methods: Eight participants enrolled in a 28-day trial of PedBotHome. Ankle strength, range of motion, and plantar flexor spasticity were measured pre- and posttrial. Performance was monitored remotely, and game settings were modified weekly by physical therapists. Results: Four participants met the study goal of 20 days of use. There were statistically significant improvements in ankle strength, spasticity, and range of motion. Conclusions: PedBotHome is a feasible device to engage children with static neurological injuries in ankle home exercise. This pilot study expands the paradigm for future innovative home-based robotic rehabilitation.